Tinjuan Yuridis Terhadap Tindak Pidana Perdagangan Orang (Studi Kasus Putusan Nomor 178/Pid.Sus/2021/PN KPG) - George Aldystra Bara; Bhisa Vitus Wilhemus; Adrianus Djara Dima (Law Faculty, Nusa Cendana University, 2026)
This research analyzes the juridical review of the crime of human trafficking, using the court decision Number 178/Pid.Sus/2021/PN KPG as a case study. The study focuses on two main aspects: (1) how criminal sanctions are applied to perpetrators of human trafficking, and (2) how the panel of judges considers legal reasoning in sentencing the perpetrator in this case. This research employs a normative-empirical juridical method. The data used are secondary data obtained through literature studies on relevant laws and court decisions.The findings show that the judge chose the third indictment to be applied to the defendant, which refers to Article 6 of Law Number 21 of 2007 on the Eradication of the Crime of Human Trafficking. The defendant was proven to have fulfilled all the elements of the crime. In their consideration, the panel of judges sentenced the defendant to five (5) years of imprisonment and ordered restitution of Rp500,000. However, the verdict reveals a discrepancy with Article 6 of Law Number 21 of 2007, which stipulates that imprisonment and fines are cumulative. In this case, the judge imposed only imprisonment without any fine. Therefore, in issuing a verdict, the panel of judges must thoroughly consider all aspects to avoid potential errors that could lead to injustice.